Study on the mechanism by which Xuanfu Hua Tang increases sensitivity of hepatocellular carcinoma cells to sorafenib by antagonizing the Notch1 pathway through HIF-2α - Luo, Wenzhao; Li, Xian; Shang, Yiwan; Chen, Zhen; Cui, Yinglin (Frontiers in Oncology, 2025)
BackgroundIt is crucial to explore ways to increase the sensitivity of hepatocellular carcinoma cells to sorafenib.MethodsThe HepG2 and Huh7 cell lines with overexpressed HIF-2α were constructed. The cells were treated with Xuanfu Hua Tang (Xuanfu HT) containing serum and sorafenib separately and by using both of them, the cell viability and other cell biology functions were detected by CCK-8 and other assays. The mechanism of quercetin was investigated by thermal stability assay and dual luciferase reporter gene assay, and the effects of Xuanfu HT on the transcript and protein levels of Notch1 pathway genes were evaluated by qPCR and Western Blot. The effects of Xuanfu HT in tumor growth was investigates by mice subcutaneous tumor implantation model.ResultsThe Xuanfu HT increased sensitivity of HepG2 and Huh7 cell lines with overexpressed HIF-2αto sorafenib, and enhanced inhibition of cell proliferation, migration, invasion and angiogenesis by sorafenib. The component quercetin of Xuanfu HT containing serum could inhibit the binding between HIF-2α and the promoter of the transcription factor FOXP3 to inhibit the expression of FOXP3, so as to inhibit the activation of Notch1 pathway and angiogenesis. The expression of FOXP3 counteracted the decrease in Notch1 and VEGF expression, and angiogenic capacity induced by the combined treatment with Xuanfu HT and sorafenib. The tumor growth inhibitory effects of Xuanfu HT and sorafenib in mice were proved by constructing a subcutaneous tumor model.ConclusionXuanfu HT can increase sorafenib sensitivity of hepatocellular carcinoma cells by antagonizing the Notch1 pathway through quercetin-binding HIF-2α.